4-(3,4-Dimethyl-5-phenyl-1,3-oxazolidin-2-yl)-2-methoxyphenol - Mohd Razip, Asaruddin; Habibah, A Wahab; Nornisah, Mohamed; Fun, Hoong-Kun (IUCR, 2010)
In the title compound, C18H21NO3, the oxazolidine ring adopts an envelope conformation with the N atom at the flap position. The two benzene rings make dihedral angles of 74.27 (14) and 73.26 (15)° with the mean plane through the oxazolidine ring. In the crystal structure, O—H⋯O and C—H⋯O hydrogen bonds connect adjacent molecules into chains along [010] incorporating R 2 2(8) loops and further stabilization is provided by weak intermolecular C—H⋯π interactions